Frequency of COVID‐19 vaccine side effects and its associated factors among the vaccinated population of Pakistan: A cross‐sectional study. Issue 1 (18th January 2023) - Yasmin, Farah; Najeeb, Hala; Siddiqui, Hasan Fareed; Asghar, Muhammad Sohaib; Awan, Hashir Ali; Usama, Rana Muhammad; Allahuddin, Zoha; Tahir, Muhammad Junaid; Ullah, Kaleem; Mahmmoud Fadelallah Eljack, Mohammed
Abstract: Background: Coronavirus disease 2019 (COVID‐19) vaccine side effects have an important role in the hesitancy of the general population toward vaccine administration. Therefore, this study was conducted to document the COVID‐19 vaccine side effects in our population. Materials and Methods: An online survey‐based, cross‐sectional study was carried out from September 1, 2021, to October 1, 2021, to document the side effects of the COVID‐19 vaccine among the general public. The questionnaire included participants' sociodemographic data, type of vaccine, comorbidities, previous COVID‐19 infection, and assessment of side effects reported by them. Results: The majority of the participants were <20 years of age (62.2%), females (74.9%), belonged to the educational sector (58.1%), residents of Sindh (65.7%), and were previously unaffected by COVID‐19 infection (73.3%). Sinovac (38.7%) followed by Sinopharm (30.4%) and Moderna (18.4%) were administered more frequently. Commonly reported side effects were injection site pain (82%), myalgia (55%), headache (46%), fatigue/malaise (45%), and fever (41%). Vaccine side effects were more likely to be reported with the first dose as compared to the second dose. On regression analysis, factors associated with occurrence of side effects included younger age (odds ratio [OR]: 6.000 [2.065–17.431], p  < 0.001), female gender (OR: 2.373 [1.146–4.914], p  = 0.020), marital status (OR: 0.217 [0.085–0.556], p  < 0.001), graduate level of education (OR: 0.353 [0.153–0.816], p  = 0.015), and occupation being either retired, freelancers, or social workers (OR: 0.310 [0.106–0.909]), p  = 0.033). Previous infection with COVID‐19 ( p  = 0.458) and comorbidities were found unrelated ( p  = 0.707) to the occurrence of side effects. Conclusion: The overall prevalence of local side effects was quite higher than the systemic ones. Further large‐scale studies on vaccine safety are required to strengthen public confidence in the vaccination drive.